Description of the immature stages of Rutela lineola (Linnaeus, 1767) (Coleoptera: Melolonthidae: Rutelinae) - Calisto, Viviana; Morelli, Enrique (Instituto de Ecología, A.C., 2011)
In the present work are described and illustrated the third-instar larva and pupa of Rutela lineola Linneo, 1767. This rutelinae is quite common in Uruguay, their larvae are xylophagous finding them inside fallen trunks. An identification key of the third-instar larvae for the Rutelinae species described in Uruguay including R. formosa and R. dorcyi, is presented.